Poliomyelitis in Pakistan: Evolving challenges and way forward (Journal of Fatima Jinnah Medical University, 2023)
Poliomyelitis, an acute paralytic illness, affects children under the age of five. It is brought on by the Polio Virus (PV), a single-stranded RNA virus that comes in three serotypes (type 1, 2, and 3) which is transmitted by feco-oral route.1,2 Since 1988, there has been a 99.9% decrease in polio cases worldwide because of the World Health Organization's Global Polio Eradication initiative.1 This initiative has played a vital role in eradication of the disease. Pakistan is one of the 2 nations where polio remains as an endemic disease even at the end of 2022, the other being Afghanistan.2          In 2021, Pakistan reported just 1 case of polio linked to the Wild Poliovirus type 1 (WPV1) against 14 cases from April 1 through July 31, 2022.2 Eleven instances of polio have been reported in the Northwestern Waziristan in 2022, clearly illustrating the loopholes in national policies to completely eradicate the disease despite its goal to immunize 12.6 million children by 2022.2 The goal of the Global Polio Eradication Initiative's (GPEI) current 5-year strategic plan is to interrupt WPV1 transmission by 2023.3                According to WHO and UNICEF estimates, in Pakistan approximately 83% of infants received three doses of the Oral Poliovirus Vaccine (OPV) and one dose of Inactivated Poliovirus Vaccine (IPV) in 2021. While none of the districts in Baluchistan, Khyber Pakhtunkhwa, and Sindh attained 80% vaccine coverage, 86% districts in Punjab province had >3 dose OPV coverage.4